Organizational climate and attitude towards unionism of union members and non-members in selected beverage companies in Iloilo city and Bacolod City - Divinagracia, Naisil Ann S
This study sought to find out the organizational climate and attitude towards unionism of union members an dnon-members of selected beverage companies namely: Coca-Cola in Iloilo City and Bacolod City and Cosmos in Iloilo City. One hundred six (106) employees served as respondents (53 union mebrs and 53 non-union members)., The Orgnaizational climate Inventory Scale by Peterson and Pace and Survey Questionnaire Items on Labor Unions and Strikes by Guidote and Dayag were used for data gathering. Responses were analyzed through frequency counting, percentage distribution, mean, standard deviation and t-test. Results showed that members and non-members of the union tend to have positive evaluation of their organizational climate. Union members have positive attitude towards unionism or in favor of labor unions while non-members were not in favor of labor unions. There was a significant difference in the attitude towards unionism of union members and non-members. It was significant because its t-computed value (t-comp=4.7) is greater than t-critical value (t-crit=1.645, df=104) in the alpha level of 0.05. The researchers recommended that the study be conducted to other industries or companies.